2020
DOI: 10.1021/acs.macromol.0c01030
|View full text |Cite
|
Sign up to set email alerts
|

Conformations and Dynamics of Polymer Chains in Cis and Trans Polybutadiene/Silica Nanocomposites through Atomistic Simulations: From the Unentangled to the Entangled Regime

Abstract: The conformations and the dynamics of poly­(butadiene) (PB) chains, of various molecular weights, in PB/silica nanocomposites are studied through long-time atomistic molecular dynamics simulations at T = 413 K, well above T g. The effect of the stereochemistry of PB chains is addressed by simulation of cis-1,4-PB/silica and trans-1,4-PB/silica nanocomposites. The model systems contain 30 wt % (≈12 vol %) silica nanoparticles (NPs) of diameter ≈4 nm. The nanocomposites are characterized through analyzing (i) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 76 publications
6
62
0
Order By: Relevance
“…Such morphological features are well known in the field of reinforced elastomers and are associated with the formation of both interfacial chemical bonds and interphase domains of higher cross-linking density. Recent computer modeling studies have shown how double bond interactions from a diene elastomer ( cis - and trans- polybutadiene) with silica nanoparticles are sufficient to bring about the formation of an interphase layer [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such morphological features are well known in the field of reinforced elastomers and are associated with the formation of both interfacial chemical bonds and interphase domains of higher cross-linking density. Recent computer modeling studies have shown how double bond interactions from a diene elastomer ( cis - and trans- polybutadiene) with silica nanoparticles are sufficient to bring about the formation of an interphase layer [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that the shift was observed for the nanocomposite systems where the radius of the nanoparticle was comparable to the Kuhn length of the polymer. The data presented in Figure 5 correspond to a system in which the radius of nanofillers is around two times bigger than the Kuhn length of the polymer matrix (see [ 54 ] for the estimation of the Kuhn length for the used PB model). The probability of finding trains formed by the whole chain, i.e., for which its length equals to the length of the polymer chain, is higher in the systems with shorter cPB30 chains than cPB100 due to the lower entropic penalty associated with the full-chain adsorption in the former case, as also reported in the literature for flat surfaces [ 35 ] and silica nanocomposites [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the long trains, the enthalpic contribution (i.e., increased number of contacts with the surface) and the connectivity effect wins over the entropic one, and the dynamics becomes slower as the length of the train increases (notice the difference in the actual values of , e.g., for trains consisting of 9 and 3 segments in Figure 11 ). By contrast, the segments of the shortest trains (up to three monomers, i.e., up to the Kuhn length [ 54 ]) are even slower than the first (terminal) monomers of the longer trains. Due to the low probability of finding long trains (see Figure 5 ), we cannot obtain statistically relevant results for much longer trains than those presented in Figure 11 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations